Six years of Sentinel-2 archive of Slovenia - Pehani, Peter (Geodetski vestnik, 2022)
The Sentinel-2 is a high resolution optical satellite mission, developed by the European Space Agency (ESA) for the European Commission. Currently the mission has two satellites in orbit: Sentinel-2A from 23rd June 2015, and Sentinel-2B from 7th March 2017. Revisit time for this twin constellation is five days. The twin satellites represent a very stable data source, but for the first six operational months (i.e. the second half of the 2015). From the very start of the mission, the Research Centre of the Slovenian Academy of Sciences and Arts (ZRC SAZU) is collecting its own archive of Sentinel-2 data for the extent of the Republic of Slovenia. The data is saved in its original processing state (Level-1C) and in four levels of processing. The archive has now been operating for six full years, which is a good milestone for a statistical overview. We analyse the archive of Sentinel-2 data of Slovenia from several aspects at the country level. A special focus is placed on cloud cover, as only cloud-free data can give an impression of the actual spatial and temporal usability of optical data.
Keywords: archive; arhiv; cloud cover; časovna vrsta satelitskih posnetkov; satelitski podatki; satellite data; satellite image time series; Sentinel-2; Slovenia; Slovenija; stopnja oblačnosti